Investment Awareness and Preferences Among Collage Going Students Towards the Stock Market - Patil, Sayali R.; Jadhav, Sudarshan D. (Bumi Publikasi Nusantara, 2022)
The stock market is a well-organized platform for various buyers and sellers to buy and sell shares. The main objective of this research is to study the awareness and the preference of students toward investment in the share market. The data used for the study are collected from primary data. This study will be helpful for the investors to become more aware and confident to invest in the stock market. This research will help to examine the awareness of investment among the students. The research is about finding out the student’s interest in investment and reasons for not investing in the share market. The research will help to measure the satisfaction level of students towards investment in the share market. Finally, the limitations and recommendations are included to help other researchers to have better findings of the results.